Studi Kasus Prestasi Belajar Rendah Siswa “NH” di Madrasah Aliyah Negeri Sakatiga Kabupaten Ogan Ilir - Wiyono, Teguh; Gani, Syarifuddin; Sofah, Rahmi (Jurnal Konseling Komprehensif: Kajian Teori dan Praktik Bimbingan dan Konseling, 2017)
This research is titled "A case study of students' low learning achievement 'NH' in the madrasah aliyah Sakatiga district of Ogan Ilir". The purpose of this study is to determine what factors are the cause of low learning achievement 'NH'. This research is case study research. The researchers collected data through observation, documentation and interviews on the subject 'NH', parents, subject teachers and homeroom, and a close friend of 'NH'. The analysis in this research using fish bone method. The results show that the low learning achievement of 'NH' is influenced by internal factors and external factors. Of the internal factors affecting 'NH' have less interest in learning and low learning motivation. From the external factor is the magnitude of the influence of parents in the selection of schools, namely 'NH' entry in Madrasah Aliyah on the desire of both parents 'NH' while 'NH' want to continue school in high school, this is one of the factors of low learning achievement 'NH'.